A lithium ion battery

By using cyclic sulfate and cyclic sulfate additives in the electrolyte of lithium-ion batteries, combined with the appropriate graphite particle size, the performance problems of lithium-ion batteries under high and low temperature conditions are solved, and the battery is significantly improved cycling and charging performance.

CN118867129BActive Publication Date: 2024-12-20SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411312914.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have poor performance under high and low temperature conditions. Sulfate additives affect high-temperature storage performance, and sulfonate additives affect low-temperature charging performance.

Method used

The electrolyte is combined with cyclic sulfate and cyclic sulfate additives, and the volume median particle size of graphite and the ratio of additives are controlled to form an appropriate interface film to improve the high-temperature circulation and low-temperature charging performance of the battery.

Benefits of technology

The performance of lithium-ion batteries under high-temperature circulation and low-temperature conditions is significantly improved, including high-temperature storage and low-temperature charging performance, which reduces diffusion impedance and side reactions through synergistic effects and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a lithium ion battery, comprising a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, the electrolyte comprises a first additive and a second additive, the first additive comprises a cyclic sulfate compound, and the second additive comprises a cyclic sulfonate compound; the battery satisfies the relationship 1: 2≤W / (A+B)≤10. In Formula 1, the first additive, the second additive and the graphite synergistically improve the high temperature storage, high temperature cycle performance and low temperature performance of the battery, and solves the problem that adding sulfonate additives or sulfate additives to the electrolyte affects the high temperature performance of the battery, and adding sulfonate additives and sulfate additives reduces the low temperature performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery. Background Art

[0002] Lithium-ion battery is a high energy density, high efficiency, environmentally friendly battery. Due to its many advantages, it has become the preferred power source for modern electronic devices and small power systems. The basic components of lithium-ion batteries include positive electrode, negative electrode, electrolyte and separator. The negative electrode is the carrier of lithium ions and electrons during the charging process of the battery, and plays the role of energy storage and release.

[0003] Lithium-ion batteries, the negative electrode includes graphite. Generally, the high-temperature performance and low-temperature performance of the battery are low. In order to improve the battery performance, electrolyte additives are generally added to the electrolyte. The electrolyte additives include sulfonate additives, sulfate additives, etc. Among them, although sulfate additives can form a stable interface film at the interface between the positive and negative electrodes, the interface film formed by sulfate additives at the positive electrode interface is thin, which affects the high-temperature storage performance of the battery; although sulfonate additives can form a thick, stable, and dense CEI film on the positive electrode side, the impedance of the formed CEI film is large, which can easily cause the positive electrode polarization to increase, resulting in excessive positive electrode potential and deterioration of high-temperature cycle performance. When sulfonate additives and sulfate additives are used in combination, the viscosity is large at low temperatures, which affects the charging performance of the battery at low temperatures and reduces the low-temperature performance of the battery. Summary of the invention

[0004] In order to solve the problem that adding sulfonate additives or sulfate ester additives to the existing battery electrolyte affects the high temperature performance of the battery, and adding sulfonate additives and sulfate ester additives reduces the low temperature performance of the battery, the present application provides a lithium ion battery.

[0005] In one aspect, the present invention provides a battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, the electrolyte comprises a first additive and a second additive, the first additive comprises a cyclic sulfate ester compound, and the second additive comprises a cyclic sulfonate ester compound;

[0006] The battery satisfies the relationship 1: 2≤W / (A+B)≤10 Formula 1

[0007] Wherein, A is the mass percentage of the first additive in the electrolyte, in units of %;

[0008] B is the mass percentage of the second additive in the electrolyte, in units of %;

[0009] W is the volume median particle size Dv50 of graphite, in μm.

[0010] Preferably, the battery satisfies the relationship 2:

[0011] 3≤W / (A+B)≤8 Formula 2.

[0012] Preferably, the mass percentage A of the first additive in the electrolyte is 0.5-4%; and / or the mass percentage B of the second additive in the electrolyte is 0.5-4%.

[0013] Preferably, the mass percentage A of the first additive in the electrolyte is 1-4%; and / or the mass percentage B of the second additive in the electrolyte is 1-4%.

[0014] Preferably, the battery also satisfies Relationship 3:

[0015] 0.25≤A / B≤4 Formula 3; 0.5≤A≤4, 0.5≤B≤4.

[0016] Preferably, the volume median particle size Dv50 of the graphite is 8 to 15 μm.

[0017] Preferably, the volume median particle size Dv50 of the graphite is 8 to 12 μm.

[0018] Preferably, the first additive comprises at least one of the following compounds:

[0019] .

[0020] Preferably, the second additive comprises at least one of the compounds represented by Structural Formula 1, Structural Formula 2, and Structural Formula 3. ;

[0021] Among them, R 1 , R 2 Each independently selected from at least one of an alkylene group having 1 to 6 carbon atoms which may be substituted by halogen and an alkenylene group having 2 to 6 carbon atoms which may be substituted by halogen.

[0022] Preferably, the second additive includes one or more of 1,3-propane sultone, propenyl-1,3-sultone, vinyl sulfate, and methylene methane disulfonate.

[0023] Preferably, the electrolyte further includes a third additive, the third additive includes a carbonate compound, and the mass percentage of the third additive in the electrolyte is 5-15%.

[0024] Preferably, the carbonate compound includes one or more of fluoroethylene carbonate, vinylene carbonate, 3,3,3-trifluoropropylene carbonate, tetrafluoroethylene carbonate, and vinyl ethylene carbonate.

[0025] Preferably, the positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese oxide, lithium manganese iron phosphate, and lithium vanadium phosphate;

[0026] The chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O 2 , wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.

[0027] The lithium-ion battery provided in the present application satisfies the relationship 1: 2≤W / (A+B)≤10. In formula 1, the first additive and the second additive synergistically improve the high-temperature storage and high-temperature cycle performance of the battery. When the volume median particle size Dv50 of the graphite is low, the lithium ion diffusion path is shorter and the diffusion impedance is lower, thereby increasing the lithium ion diffusion rate of the battery at low temperatures. The first additive, the second additive and the graphite synergize, significantly taking into account the low-temperature charging performance of the battery, and jointly improving the high-temperature cycle, high-temperature storage and low-temperature performance of the battery. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] In order to illustrate the technical solution of the present invention, specific embodiments are provided below for illustration.

[0030] On the one hand, an embodiment of the present application provides a lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, the electrolyte comprises a first additive and a second additive, the first additive comprises a cyclic sulfate ester compound, and the second additive comprises a cyclic sulfonate ester compound;

[0031] The battery satisfies the relationship 1: 2≤W / (A+B)≤10 Formula 1

[0032] Wherein, A is the mass percentage of the first additive in the electrolyte, in units of %;

[0033] B is the mass percentage of the second additive in the electrolyte, in units of %;

[0034] W is the volume median particle size Dv50 of graphite, in μm.

[0035] Specifically, the volume median particle size refers to the particle size corresponding to 50% of the cumulative volume in the volume cumulative distribution of powder particles. The volume median particle size can be obtained by testing with a particle size analyzer. This parameter reflects the median size of the powder particles, which means that half of the particle volume is smaller than this particle size, and the other half of the particle volume is larger than this particle size.

[0036] The volume median particle size Dv50 of graphite reflects the average size of graphite, which can determine the diffusion path of lithium ions inside the graphite particles and affect the specific surface area of ​​the graphite particles, directly affecting the fast charging performance and cycle performance of the graphite. Under the same mass, the lower the volume median particle size of the graphite, the shorter the lithium ion diffusion path, the lower the diffusion impedance, and the larger the specific surface area. Low diffusion impedance is conducive to the rapid charging and discharging of graphite particles, and is also beneficial to improving the low-temperature rate performance of the battery. A large specific surface area will lead to more side reactions with the electrolyte, and reduced high-temperature cycle performance and high-temperature storage performance.

[0037] The first additive includes a cyclic sulfate compound, which can form a stable SEI film at the negative electrode interface. The SEI film is rich in alkyl sulfonate lithium, which can effectively prevent the negative electrode surface from reacting with the electrolyte, and can significantly reduce the impact of the small graphite particle size in the negative electrode sheet on the battery performance, and improve the battery cycle performance. The first additive can also form a dense and thin CEI film at the positive electrode. The CEI film is not easy to decompose and has a low impedance under high voltage. The impedance of the positive electrode side can be reduced in high-voltage and high-temperature cycles, thereby reducing the positive electrode polarization, avoiding the positive electrode potential from being too high to cause the positive electrode active material to decompose, and then improve the high-temperature cycle performance. Because the CEI film formed by the first additive at the positive electrode is thin, the effect of improving high-temperature storage is not obvious. The second additive includes a cyclic sulfonate additive, which can form a stable, dense, and thick CEI film on the positive electrode side. The CEI film is extremely resistant to high temperatures, so it can significantly improve high-temperature storage, but the second additive forms a CEI film with a large impedance on the positive electrode side, which is easy to cause the positive electrode polarization to increase, resulting in excessive positive electrode potential and deterioration of high-temperature cycle performance. Therefore, the combined use of the first additive and the second additive can have a synergistic effect and significantly improve the high temperature storage and high temperature cycle performance of the battery. However, the viscosity of the first additive and the second additive is relatively large at low temperatures, and the viscosity of the electrolyte increases, thereby deteriorating the charging performance at low temperatures.

[0038] The lithium-ion battery provided in the present application satisfies the relationship 1: 2≤W / (A+B)≤10. In formula 1, the first additive and the second additive synergistically improve the high-temperature storage and high-temperature cycle performance of the battery. When the volume median particle size Dv50 of the graphite is low, the lithium ion diffusion path is shorter and the diffusion impedance is lower, thereby increasing the lithium ion diffusion rate of the battery at low temperatures. The first additive, the second additive and the graphite synergize, significantly taking into account the low-temperature charging performance of the battery, and jointly improving the high-temperature cycle, high-temperature storage and low-temperature performance of the battery.

[0039] If W / (A+B) is less than 2, the amount of the first additive and the second additive added is too much, the viscosity of the electrolyte increases, affecting the transmission rate of lithium ions and reducing the low-temperature charging performance of the battery; or the volume median particle size Dv50 of the graphite is too small, the specific surface area of ​​the graphite particles is large, the side reactions increase, and it is unable to cooperate with the first additive and the second additive, and the high-temperature performance of the battery is reduced. If W / (A+B) is greater than 10, the volume median particle size Dv50 of the graphite is too large, the graphite particles are too large, the diffusion path of lithium ions inside the graphite particles increases, affecting the diffusion rate of lithium ions in the graphite, and the low-temperature charging performance of the battery is reduced; or the amount of the first additive and the second additive added is too small, and they cannot play a good synergistic role to prevent the deterioration of the high-temperature performance of the battery, and the high-temperature cycle performance and high-temperature storage performance of the battery are low.

[0040] Specifically, the value of W / (A+B) may be in the range of 2-4, 4-6, 6-8 or 8-10.

[0041] In some preferred embodiments, the battery satisfies the relationship 2:

[0042] 3≤W / (A+B)≤8 Formula 2.

[0043] Specifically, the battery satisfies equation 2, the first additive and the second additive synergistically improve the high temperature cycle and high temperature storage performance of the battery, and at the same time, the first additive, the second additive and graphite synergize to significantly take into account the low temperature charging performance of the battery, while significantly improving the high temperature storage and high temperature cycle performance of the battery.

[0044] In some embodiments, the mass percentage A of the first additive in the electrolyte is 0.5-4%.

[0045] Specifically, the content of the first additive is in the range of 0.5~4%, and it can cooperate with the second additive and graphite to form a stable SEI film at the negative electrode interface, effectively prevent the side reaction between the negative electrode surface and the electrolyte, and can significantly reduce the impact of the small graphite particle size in the negative electrode sheet on the battery performance, and improve the high-temperature cycle performance of the battery; cooperate with the second additive to form a dense and moderately thick CEI film at the positive electrode, improve the high-temperature cycle performance, low-temperature charge and discharge performance and high-temperature storage performance of the battery.

[0046] If the content of the first additive is less than 0.5%, the amount of the first additive added is too little, the SEI film formed at the negative electrode interface is thin and has low stability, and cannot effectively prevent the side reaction between the negative electrode and the electrolyte, and the high-temperature cycle performance of the battery is reduced. If the content of the first additive is higher than 4%, the thickness of the SEI film formed at the negative electrode interface is too large, the interface film impedance increases, the battery polarization increases, and the high-temperature cycle performance of the battery is reduced.

[0047] The mass percentage A of the first additive in the electrolyte can be 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.7%, 2.0%, 2.4%, 2.8%, 3.0%, 3.5%, 4.0%, etc., as long as A is in the range of 0.5~4%.

[0048] In some preferred embodiments, the mass percentage A of the first additive in the electrolyte is 1-4%.

[0049] Specifically, the content of the first additive is in the range of 1-4%, which can cooperate with the second additive and graphite to be more conducive to improving the high-temperature cycle, high-temperature storage and low-temperature charge and discharge performance of the battery.

[0050] In some embodiments, the first additive includes at least one of the following compounds: .

[0051] It should be noted that the above compounds 1-1 to 1-12 are some of the cyclic sulfate ester compounds, and any compound may be used as long as it belongs to the cyclic sulfate ester class.

[0052] In some embodiments, the mass percentage B of the second additive in the electrolyte is 0.5-4%.

[0053] Specifically, the mass content of the second additive is in the range of 0.5-4%, and cooperates with the first additive to form a stable, dense, and moderately thick CEI film on the positive electrode side, improving the high temperature storage and high temperature cycle performance of the battery, and cooperates with graphite to improve the low temperature charge and discharge performance of the battery. Specifically, the mass content B of the second additive can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%, as long as B is in the range of 0.5%-4%.

[0054] If the content of the second additive is too low, the interface film thickness on the positive electrode side is too small, and the high-temperature cycle performance and high-temperature storage performance of the battery are reduced; if the content of the second additive is too high, the interface film thickness on the positive electrode side is too thick, and the CEI film impedance is large, which can easily cause the positive electrode polarization to increase, resulting in excessively high positive electrode potential, which deteriorates the high-temperature cycle and high-temperature storage performance.

[0055] In some preferred embodiments, the mass percentage B of the second additive in the electrolyte is 1-4%.

[0056] Specifically, the content of the second additive is in the range of 1-4%, which can cooperate with the first additive and graphite to improve the high-temperature cycle, high-temperature storage and low-temperature charge and discharge performance of the battery.

[0057] In some embodiments, the second additive includes at least one of the compounds shown in Structural Formula 1, Structural Formula 2, and Structural Formula 3. ;

[0058] Among them, R 1 , R 2 Each independently selected from at least one of an alkylene group having 1 to 6 carbon atoms which may be substituted by halogen and an alkenylene group having 2 to 6 carbon atoms which may be substituted by halogen.

[0059] Specifically, as long as the second additive satisfies structural formulas 1, 2, and 3, it can cooperate with the first additive and graphite to improve the high-temperature cycle, high-temperature storage, and low-temperature charge and discharge performance of the battery.

[0060] Halogen includes fluorine, chlorine, bromine, iodine, etc. Alkylene with 1 to 6 carbon atoms includes straight chain alkylene or branched alkylene, such as methylene, ethylene, etc. Alkenylene with 2 to 6 carbon atoms includes straight chain alkenylene or branched alkenylene.

[0061] In some embodiments, the second additive includes one or more of 1,3-propane sultone, propenyl-1,3-sultone, vinyl sulfate, and methylene methane disulfonate.

[0062] Specifically, the second additive is preferably of the type mentioned above, which is more conducive to improving the high-temperature cycle performance and high-temperature storage performance of the battery.

[0063] In some embodiments, the volume median particle size Dv50 of the graphite is 8-15 μm.

[0064] Specifically, the volume median particle size Dv50 of graphite is in the range of 8 to 15 μm, and the diffusion impedance of lithium ions inside the graphite particles is low, which is beneficial to improving the low-temperature charging performance of the battery. The graphite has a large specific surface area and can work together with the first additive and the second additive to improve the high-temperature cycle, high-temperature storage and low-temperature performance of the battery.

[0065] In some preferred embodiments, the volume median particle size Dv50 of the graphite is 8-12 μm.

[0066] Specifically, when the volume median particle size Dv50 of graphite is in the range of 8 to 12 μm, the low-temperature charge and discharge performance of the battery is better and the low-temperature discharge capacity retention rate is higher.

[0067] In some embodiments, the battery further satisfies Relationship 3:

[0068] 0.25≤A / B≤4 Formula 3;

[0069] 0.5≤A≤4, 0.5≤B≤4;

[0070] Wherein, A is the mass percentage of the first additive in the electrolyte, in units of %;

[0071] B is the mass percentage of the second additive in the electrolyte, in %.

[0072] Specifically, the ratio of A / B is in the range of 0.25 to 4, which is more conducive to the synergistic effect of the first additive and the second additive, thereby improving the high temperature cycle performance and high temperature storage performance of the battery.

[0073] In some embodiments, the electrolyte further includes a third additive, the third additive includes a carbonate compound, and the mass percentage of the third additive in the electrolyte is 5-15%.

[0074] Specifically, the third additive is also conducive to the formation of a more stable SEI film at the negative electrode interface in cooperation with the first additive, thereby improving the battery's cycle performance. If the content of the third additive is too high, the side reactions will increase and the battery will produce too much gas; if the content of the third additive is too low, the formation of the negative electrode interface film will be affected, thereby reducing the battery's cycle performance.

[0075] In some embodiments, the carbonate compound includes one or more of fluoroethylene carbonate, vinylene carbonate, 3,3,3-trifluoropropylene carbonate, tetrafluoroethylene carbonate, and vinyl ethylene carbonate.

[0076] Specifically, the third additive is preferably of the type mentioned above, which helps to form an SEI film with a stable interface and improve the cycle performance of the battery.

[0077] In some embodiments, the electrolyte also includes a solvent, and the solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0078] Specifically, the above-mentioned solvent types are selected to mainly dissolve the first additive, the second additive, the third additive and the lithium salt.

[0079] In some embodiments, the electrolyte further includes a lithium salt.

[0080] Lithium salts are prior art and are not limited in this application. For example, the lithium salt may be at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium difluorobis(oxalatoborate).

[0081] It should be noted that the present application does not specifically limit the method for preparing the electrolyte, and those skilled in the art can prepare it into an electrolyte according to conventional technical means, for example, by uniformly mixing the raw materials according to a proportion.

[0082] In some embodiments, the positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese oxide, lithium manganese iron phosphate, and lithium vanadium phosphate;

[0083] The chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2 , wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.

[0084] Specifically, the positive electrode active material may be selected from one or more of the above.

[0085] The negative electrode active material includes graphite, wherein the graphite can be at least one of natural graphite and artificial graphite.

[0086] In some embodiments, the negative electrode active material further comprises mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy.

[0087] In the present invention, there is no particular limitation on the negative electrode current collector as long as the purpose of the present application can be achieved. For example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper or a composite current collector.

[0088] In some preferred embodiments, the negative electrode current collector comprises copper foil.

[0089] In some embodiments, the negative electrode further includes a negative electrode active material layer, the negative electrode active material layer is disposed on at least one side surface of the current collector, and the negative electrode active material layer further includes a negative electrode conductor, a negative electrode binder, a thickener and a solvent.

[0090] The negative electrode conductive agent includes at least one of natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, graphene and other carbon materials. The negative electrode binder includes styrene butadiene latex and the thickener includes CMC and the solvent includes deionized water.

[0091] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0092] In the present application, the type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In one embodiment, the positive electrode current collector is a metal material.

[0093] In some embodiments, the positive electrode active material layer further includes a positive electrode conductor, a positive electrode binder, and a solvent.

[0094] In some embodiments, the type of the positive electrode conductive agent mentioned in the present invention is not limited, and any known conductive agent can be used.

[0095] In some embodiments, the positive electrode conductive agent mentioned in the present invention includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0096] In one embodiment, the type of the positive electrode binder mentioned in the present invention is not limited, and any known positive electrode binder can be used.

[0097] In some embodiments, the positive electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0098] In the lithium-ion battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. There is no particular restriction on the material and shape of the separator, as long as the effect of the present application is not significantly impaired.

[0099] In some embodiments, the diaphragm includes a porous sheet or non-woven fabric-like material with excellent liquid retention, and the diaphragm includes a resin or glass fiber diaphragm material, and the resin or glass fiber diaphragm material includes but is not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc.

[0100] In some embodiments, the lithium-ion battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0101] In some embodiments, the outer packaging of the lithium ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0102] The present application has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square, or any other shape.

[0103] On the other hand, an embodiment of the present application provides an electrical device, comprising the lithium-ion battery described above.

[0104] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0105] The present invention is further described below by way of examples.

[0106] Example 1

[0107] Preparation of positive electrode

[0108] The positive electrode active material lithium cobalt oxide, the positive electrode conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are evenly mixed in a mass ratio of 97:1.5:1.5, and evenly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.

[0109] Preparation of negative electrode

[0110] The negative electrode active material graphite, negative electrode conductive agent acetylene black (Super P), thickener CMC and negative electrode binder SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed with deionized water to form a uniform negative electrode slurry. The mixed slurry is coated on both sides of the copper foil current collector, and then baked, rolled, and cut into pieces to obtain a negative electrode sheet. The specific value of the volume median particle size Dv50 of the added graphite is shown in Table 1.

[0111] Preparation of electrolyte

[0112] a. Ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP) and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, and water was removed by molecular sieves for standby use. 1M LiPF 6 Mix well;

[0113] b. Add additives (the types and amounts of additives are shown in Table 1) to the colorless transparent liquid obtained in step a to obtain an electrolyte.

[0114] Lithium-ion battery manufacturing

[0115] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and the bare battery cell is obtained by winding and welding the tabs. The bare battery cell is placed in an aluminum-plastic film, liquid is injected, and packaged to obtain a lithium-ion battery.

[0116] Examples 2 to 26 and Comparative Examples 1 to 14

[0117] Most of the steps of Examples 2 to 26 and Comparative Examples 1 to 14 are the same as those of Example 1, except that the types and contents of additives in the electrolyte are different, as shown in Table 1; the volume median particle size Dv50 of the graphite added in the preparation of the negative electrode sheet is different, and the specific values ​​are shown in Table 1.

[0118] Embodiment 27

[0119] Most of the steps of Example 27 are the same as those of Example 1, except that a third additive, fluoroethylene carbonate, is added to the electrolyte, and the mass content of the third additive in the electrolyte is 6%. The rest is the same as Example 1.

[0120] The test method for the volume median particle size Dv50 of graphite is as follows:

[0121] The sample particles were dispersed in a liquid medium at a concentration of 200 to 300 mg / L to obtain a mixture.

[0122] The optical diffraction particle size analyzer (MS2000) allows a monochromatic light beam to pass through the mixture; after the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values ​​of the scattering diagram at many angles and records these values ​​for analysis. The Rayleigh scattering formula is used to calculate the scattering values ​​to obtain the ratio of the volume of particles of each size level to the total volume, thereby obtaining the volume distribution of the particle size.

[0123] Table 1

[0124]

[0125] Performance Testing

[0126] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to the following tests.

[0127] 60℃ storage performance test

[0128] The lithium-ion batteries prepared in the above embodiments and comparative examples were charged at a rate of 1C to a cut-off voltage and a cut-off current of 0.025C at 25°C, left to stand for 5 minutes, and the thickness H1 of the lithium-ion batteries was tested; thereafter, the batteries were stored at 60°C for 60 days, and the thickness H2 of the lithium-ion batteries was tested after the charge was completed.

[0129] Thickness expansion ratio = [(H2-H1) / H1] x 100%.

[0130] 45℃ Cyclic Performance Test

[0131] The lithium ion batteries prepared in the above embodiments and comparative examples were charged and discharged at 45°C at a rate of 1C / 1C within the charge and discharge cut-off voltage range. The discharge capacity of the first week of the test was counted as C1, and the discharge capacity of the Nth cycle was counted as C2. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R2=C2 / C1 of the Nth week, and the cycle number of the lithium ion battery when the cycle capacity retention rate R2 was 70% was recorded.

[0132] -20℃ charge capacity retention rate

[0133] The lithium ion batteries prepared in the above embodiments and comparative examples were charged and discharged for 3 times at 25°C at a rate of 1C / 1C within the charge and discharge cut-off voltage range, and the charge capacity of the third week of the test was counted as C3; then the lithium ion batteries were charged and discharged for 3 times at a rate of 1C / 1C within the charge and discharge cut-off voltage range at -20°C, and the charge capacity of the third week of the test was counted as C4;

[0134] -20℃ charging capacity retention rate = C4 / C3×100%.

[0135] The above test results are shown in Table 2.

[0136] Table 2

[0137]

[0138] According to Table 1 and Table 2, when comparing Example 1 with Comparative Examples 1 to Comparative Examples 9, there is no first additive and the second additive in Comparative Example 1, and the thickness expansion rate of the battery is high, the cycle life is low, and the low-temperature charging capacity retention rate is low. The first additive is added in Comparative Example 2, and the second additive is added in Comparative Example 3, and the performance of the battery is not significantly improved. Although the first additive and the second additive are added in Comparative Examples 4 to Comparative Examples 9, the low-temperature charging performance of the battery is still poor, indicating that the first additive and the second additive are added to the electrolyte at the same time, and the battery satisfies the relationship 1: 2≤W / (A+B)≤10, where A is the first additive. The first additive and the second additive synergistically improve the high temperature storage and high temperature cycle performance of the battery. When the volume median particle size Dv50 of the graphite is low, the lithium ion diffusion path is shorter and the diffusion impedance is lower, thereby increasing the lithium ion diffusion rate of the battery at low temperatures. The first additive, the second additive and the graphite synergistically take into account the low temperature charging performance of the battery, thereby increasing the high temperature cycle life of the battery, reducing the high temperature storage thickness expansion rate, and increasing the low temperature charging capacity retention rate of the battery.

[0139] Comparing Example 1 with Comparative Examples 12 to 15, even if the mass percentage A of the first additive in the electrolyte is in the range of 0.5% to 4%, the mass percentage B of the second additive in the electrolyte is in the range of 0.5% to 4, and the volume median particle size Dv50 of the graphite is in the range of 8 to 15 μm, the battery does not satisfy the relationship 2≤W / (A+B)≤10, the battery has a small number of high-temperature cycles, a high-temperature storage thickness expansion rate, and a low-temperature charging capacity.

[0140] Comparing Example 1 to Example 5 with Example 6 to Example 7, comparing Example 8 to Example 10 with Example 11 to Example 12, and comparing Example 17 to Example 19 with Example 20 to Example 21, the mass percentage A of the first additive in the electrolyte is in the range of 0.5% to 4%, the mass percentage B of the second additive in the electrolyte is in the range of 0.5% to 4, the volume median particle size Dv50 of the graphite is in the range of 8 to 15 μm, and the relationship 2≤W / (A+B)≤10 is satisfied, the battery has a high temperature cycle life, a low high temperature storage thickness expansion rate, and a high low temperature charging capacity retention rate. By comparing Example 1 to Example 5, Example 8 to Example 10, and Example 17 to Example 19, when A is in the range of 0.5% to 4%, B is in the range of 0.5% to 4%, and W is in the range of 8 to 15 μm, the battery satisfies the relationship 3≤W / (A+B)≤8, and the high-temperature cycle and high-temperature storage of the battery are improved more significantly, and the low-temperature charge capacity retention rate of the battery is higher; further, when A is in the range of 1% to 4%, B is in the range of 1% to 4%, and W is in the range of 8 to 12 μm, the battery has a higher high-temperature cycle life, a lower high-temperature storage thickness expansion rate, and a higher low-temperature charge capacity retention rate.

[0141] Comparing Example 1 to Example 5, Example 8 to Example 10, Example 17 to Example 19 and Example 13 to Example 16, A is in the range of 0.5% to 4%, B is in the range of 0.5% to 4%, and W is in the range of 8 to 15 μm. The battery not only satisfies the relationship 2≤W / (A+B)≤10, but also satisfies the relationship 0.25≤A / B≤4. The battery has a higher high-temperature cycle life, a lower high-temperature storage thickness expansion rate, and a higher low-temperature charging capacity retention rate.

[0142] Comparing Example 1 with Example 22 to Example 26, by changing the types of the first additive and the second additive, as long as the first additive is a cyclic sulfate compound, the second additive includes a cyclic sulfonate compound, or the compound type of the second additive satisfies at least one of Structural Formula 1, Structural Formula 2, and Structural Formula 3, they all have the same effect, and can improve the high-temperature cycle life of the battery, reduce the high-temperature storage thickness expansion rate, and improve the low-temperature charging capacity retention rate of the battery.

[0143] Comparing Example 1 with Comparative Examples 10 to 11, the first additive does not belong to the cyclic sulfate ester compound, and / or the second additive does not belong to the cyclic sulfonate ester compound, or the compound selection type of the second additive does not satisfy at least one of Structural Formula 1, Structural Formula 2, and Structural Formula 3, the high temperature cycle performance, high temperature storage performance, and low temperature performance of the battery are poor.

[0144] Comparing Example 1 and Example 27, a third additive is added to the electrolyte. The third additive can cooperate with the first additive to form a more stable SEI film at the negative electrode interface, further improving the high-temperature cycle performance and low-temperature charging capacity retention rate of the battery, and reducing the high-temperature storage thickness expansion rate of the battery.

[0145] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, and the electrolyte comprises a first additive and a second additive. The battery satisfies the relationship 1: 2≤W / (A+B)≤10 Formula 1 Wherein, A is the mass percentage of the first additive in the electrolyte, in units of %; B is the mass percentage of the second additive in the electrolyte, in units of %; W is the volume median particle size Dv50 of graphite, in μm; The first additive includes a cyclic sulfate compound, and the first additive includes at least one of the following compounds: ; The second additive includes a cyclic sulfonate compound, and the second additive includes at least one of the compounds shown in Structural Formula 2 and Structural Formula 3. ; Wherein, R2 is independently selected from at least one of an alkylene group having 1 to 6 carbon atoms, which is substituted or unsubstituted by halogen, and an alkenylene group having 2 to 6 carbon atoms, which is substituted or unsubstituted by halogen; The battery also satisfies Relation 3: 0.25≤A / B≤4 Formula 3; 0.5≤A≤4, 0.5≤B≤4; The volume median particle size Dv50 of graphite is 8~15μm.

2. The lithium-ion battery according to claim 1, characterized in that The battery satisfies the relationship 2: 3≤W / (A+B)≤8 Formula 2.

3. The lithium-ion battery according to claim 1, characterized in that The mass percentage A of the first additive in the electrolyte is 1-4%; and / or the mass percentage B of the second additive in the electrolyte is 1-4%.

4. The lithium-ion battery according to claim 1, characterized in that: The volume median particle size Dv50 of graphite is 8~12μm.

5. The lithium-ion battery according to claim 1, characterized in that: The second additive includes one or more of 1,3-propane sultone, propenyl-1,3-sultone, vinyl sulfate, and methylene methane disulfonate.

6. The lithium-ion battery according to claim 1, characterized in that The electrolyte further includes a third additive, the third additive includes a carbonate compound, and the mass percentage of the third additive in the electrolyte is 5-15%.

7. The lithium-ion battery according to claim 6, characterized in that: The carbonate compound includes one or more of fluoroethylene carbonate, vinylene carbonate, 3,3,3-trifluoropropylene carbonate, tetrafluoroethylene carbonate, and vinyl ethylene carbonate.

8. The lithium-ion battery according to claim 1, characterized in that The positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese oxide, lithium manganese iron phosphate, and lithium vanadium phosphate; The chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.